Signals of resilience to ocean change: high thermal tolerance of early stage Antarctic sea urchins (Sterechinus neumayeri) reared under present-day and future pCO2 and temperature - Lydia Kapsenberg; Gretchen E Hofmann (PANGAEA, 2014)
We tested the hypothesis that development of the Antarctic urchin Sterechinus neumayeri under future ocean conditions of warming and acidification would incur physiological costs, reducing the tolerance of a secondary stressor. The aim of this study is twofold: (1) quantify current austral spring temperature and pH near sea urchin habitat at Cape Evans in McMurdo Sound, Antarctica and (2) spawn S. neumayeri in the laboratory and raise early developmental stages (EDSs) under ambient (-0.7 °C; 400 μatm pCO2) and future (+2.6 °C; 650 and 1,000 μatm pCO2) ocean conditions and expose four EDSs (blastula, gastrula, prism, and 4-arm echinopluteus) to a one hour acute heat stress and assess survivorship. Results of field data from 2011 to 2012 show extremely stable inter-annual pH conditions ranging from 7.99 to 8.08, suggesting that future ocean acidification will drastically alter the pH-seascape for S. neumayeri. In the laboratory, S. neumayeri EDSs appear to be tolerant of temperatures and pCO2 levels above their current habitat conditions. EDSs survived acute heat exposures >20 °C above habitat temperatures of -1.9 °C. No pCO2 effect was observed for EDSs reared at -0.7 °C. When reared at +2.6 °C, small but significant pCO2 effects were observed at the blastula and prism stage, suggesting that multiple stressors are more detrimental than single stressors. While surprisingly tolerant overall, blastulae were the most sensitive stage to ocean warming and acidification. We conclude that S. neumayeri may be unexpectedly physiologically tolerant of future ocean conditions.